The role of radiotherapy in the treatment of early breast cancer - Matuszewska, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2002)
The influence of radiotherapy on the results of treatment of patients after mastectomy has been a subject of clinical trials for many years. First trials indicated a significant reduction of loco-regional recurrence rate, but the influence on survival was doubtful. Recent trials have clearly demonstrated that adjuvant radiotherapy improves the loco-regional control and prolongs overall survival in patients who received systemic treatment due to axillary lymph node metastases. The improvement in the results of adjuvant radiotherapy in breast cancer is possibly related to more common use of systemic treatment and better radiotherapy techniques. The latter factor decreased the frequency of late side effects of radiation therapy, particularly the coronary heart disease, which was the main reason of increased mortality observed in irradiated patients in the era of ortovoltage equipment. Nowadays, breast cancer radiotherapy should be primarily carried out using megavoltage photons and electrons. Modern treatment planning techniques are obligatory, including radiation beam simulation and computer-aided dose calculations. The use of CT-scanning in treatment planning is sure to grow in importance in coming years, because maximal protection of normal tissues (e. g. heart and lungs) is especially important. The application of 50 Gy in 25 2-Gy fractions has been adopted as the standard prescription for adjuvant radiotherapy of large volumes (breast, chest wall, nodal areas). Breast irradiation is an accepted standard of care in all patients after breast-conserving surgery. It reduces the risk of intramammary tumor recurrence and enables breast preservation in the majority of patients. Randomised trials have established that survival rates after conservative surgery and breast irradiation are equivalent to those observed after modified radical mastectomy. In most of the patients after breast-conserving surgery only the breast is irradiated using the dose of 50 Gy in 25 fractions. Boost doses to smaller volumes at higher risk of recurrence are usually advised and consist of 10-20 Gy fractionated external beam radiotherapy or brachytherapy. Recently published EORTC trial confirmed that the boost to the tumor bed improves local control. Due to application of modern surgery and radiotherapy techniques good cosmetic results are obtained in approximately 90 proc. of patients. The issues of optimal indications for adjuvant radiotherapy, regions to treat and the accurate sequence of radio- and chemotherapy remain controversial and need to be solved in future randomised trials.